2002
DOI: 10.1093/alcalc/37.6.566
|View full text |Cite
|
Sign up to set email alerts
|

Platelet Monoamine Oxidase B Activity as a State Marker for Alcoholism: Trend Over Time During Withdrawal and Influence of Smoking and Gender

Abstract: MAO-B can be regarded as a state marker of alcohol consumption. The temporal pattern of platelet MAO-B activity may be used for the diagnostic assessment of alcoholism and early abstinence, regardless of gender and smoking status.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 45 publications
1
15
0
Order By: Relevance
“…Others (Takahashi et al, 1976;Brown, 1977) reported that the low platelet MAO activity returned to normal levels after episodes of alcoholism had subsided. As observed in smoking cessation, the activity of MAO in platelets of alcohol-dependent subjects (type of alcoholism was not further specified) increased by 40% after 8 days of alcohol withdrawal, and attained control values that remained stable thereafter (15 to 22 days of abstinence) (Coccini et al, 2002). This temporal pattern remained after correction for smoking and gender.…”
Section: Mao and Withdrawal From Alcoholmentioning
confidence: 71%
“…Others (Takahashi et al, 1976;Brown, 1977) reported that the low platelet MAO activity returned to normal levels after episodes of alcoholism had subsided. As observed in smoking cessation, the activity of MAO in platelets of alcohol-dependent subjects (type of alcoholism was not further specified) increased by 40% after 8 days of alcohol withdrawal, and attained control values that remained stable thereafter (15 to 22 days of abstinence) (Coccini et al, 2002). This temporal pattern remained after correction for smoking and gender.…”
Section: Mao and Withdrawal From Alcoholmentioning
confidence: 71%
“…The premise is sufficiently established to allow a platelet protein biochip, developed for detection of an Alzheimer's disease-specific phenotype, to include MAO B (Veitinger et al, 2014a, Veitinger et al, 2014b. This technical advance in diagnosis could be expanded for other neuropathologies or behavior with known associations to MAO B, for example, alcoholism (Coccini et al, 2002).…”
Section: Expressed Protein Levelsmentioning
confidence: 99%
“…Having in mind a number of factors that could influence MAO activity, such large interstudy variability may reflect certain methodological biases. For example, an increase in MAO activity a week after withdrawal (in fact -a return to the normal values) reported by Coccini et al [40] , may be due to higher leukocyte contamination of alcoholic plasma samples (MAO activity in that study was related to the protein content; see discussion on this issue bellow), inadequate adjusting for smoking (not recorded in the control group), gender (disproportionate representation among groups), or something else. In a recent review of the subject [36] , the need to study the effect of alcohol withdrawal on MAO-B activity in type 2 alcoholics that were controlled for smoking was emphasized.…”
Section: Discussionmentioning
confidence: 79%